2015
DOI: 10.1007/978-3-319-20086-6_30
|View full text |Cite
|
Sign up to set email alerts
|

A Solution Merging Heuristic for the Steiner Problem in Graphs Using Tree Decompositions

Abstract: Abstract. Fixed parameter tractable algorithms for bounded treewidth are known to exist for a wide class of graph optimization problems. While most research in this area has been focused on exact algorithms, it is hard to find decompositions of treewidth sufficiently small to make these algorithms fast enough for practical use. Consequently, tree decomposition based algorithms have limited applicability to large scale optimization. However, by first reducing the input graph so that a small width tree decomposi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…Since we do not know the composition of the quasispecies beforehand, we combine the results of all three heuristics into one set of candidate haplotypes for further optimization. Earlier work has shown that merging a pool of high quality approximations allows for efficient solutions to well-known optimization problems [43,44]. We compare performance of our combined approach and the individual greedy heuristics in the Supplementary Material.…”
Section: Greedy Path Extractionmentioning
confidence: 99%
“…Since we do not know the composition of the quasispecies beforehand, we combine the results of all three heuristics into one set of candidate haplotypes for further optimization. Earlier work has shown that merging a pool of high quality approximations allows for efficient solutions to well-known optimization problems [43,44]. We compare performance of our combined approach and the individual greedy heuristics in the Supplementary Material.…”
Section: Greedy Path Extractionmentioning
confidence: 99%
“…Ưu điểm của các thuật toán heuristic là thời gian chạy nhanh hơn nhiều so với các thuật toán metaheuristic. Giải pháp này thường được lựa chọn với các đồ thị có kích thước lớn [11,20,21,25].…”
Section: Các Thuật Toán Heuristicunclassified
“…Heuristic algorithms yield acceptable solutions, which might not be the best solution, in the permissible time. Optimal running time can be achieved with this class of algorithms [9,10,11].…”
Section: Related Workmentioning
confidence: 99%